Analisis Faktor Penawaran Kentang di Provinsi Sumatera Utara (Periode 2003-2012) - Boanerges Putra Sipayung; Rahmanta Ginting (Fakultas Pertanian, Universitas Timor, 2019)
The purpose of this study is to analyze the factors that influence the supply of potatoes in North Sumatra Province. The data used is time series data per two months starting from 2003 to 2012. The analytical method used is multiple regression analysis with OLS (Ordinary Least Square) model, analyzed by Eviews 8. The results of statistical estimation and econometric regression results can be used as a model for offering potatoes in North Sumatra Province. The results of the bid analysis that the price of cassava and harvested area had a significant effect on the supply of potatoes in North Sumatra Province.